2017
DOI: 10.1371/journal.pone.0182655
|View full text |Cite
|
Sign up to set email alerts
|

Redox-mediated quorum sensing in plants

Abstract: The rhizosphere, the narrow zone of soil around plant roots, is a complex network of interactions between plants, bacteria, and a variety of other organisms. The absolute dependence on host-derived signals, or xenognosins, to regulate critical developmental checkpoints for host commitment in the obligate parasitic plants provides a window into the rhizosphere’s chemical dynamics. These sessile intruders use H2O2 in a process known as semagenesis to chemically modify the mature root surfaces of proximal host pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Therefore, it is possible that the observed H 2 O 2 accumulated at later stages of haustorium formation may represent its developmental function on cell growth, that involves cell wall modification and expansion. Previous studies in Striga asiatica reported that H 2 O 2 strongly accumulated at the radicle tip and disappeared about 2 h after HIF treatment (Keyes et al, 2007; Fuller et al, 2017). In contrast to this, we observed almost no H 2 O 2 fluorescence at the radicle tip before the haustorium induction treatment, with major H 2 O 2 accumulation appearing after 10–15 h of haustorium induction (Figure 3).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it is possible that the observed H 2 O 2 accumulated at later stages of haustorium formation may represent its developmental function on cell growth, that involves cell wall modification and expansion. Previous studies in Striga asiatica reported that H 2 O 2 strongly accumulated at the radicle tip and disappeared about 2 h after HIF treatment (Keyes et al, 2007; Fuller et al, 2017). In contrast to this, we observed almost no H 2 O 2 fluorescence at the radicle tip before the haustorium induction treatment, with major H 2 O 2 accumulation appearing after 10–15 h of haustorium induction (Figure 3).…”
Section: Discussionmentioning
confidence: 92%
“…Here the production of H 2 O 2 at the parasite root tip is proposed to create a mild wound response via peroxidase oxidation of wall phenols in the host in order to generate the haustorial inducing benzoquinone at the host/parasite interface ( Chang and Lynn, 1986 ; Keyes et al., 2007 ). The parasite has been shown to have low phenol content in its own cell wall to avoid self-response, and this concept has been generalized to root meristematic tissue of other dicots including tobacco ( Fuller et al., 2017 ). In contrast to mature tobacco tissue, two-week-old tobacco seedlings failed to induce AB650 wt or YHL301 ss (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The plant root provides reduced carbon and dioxygen to the rhizosphere ( Walker et al., 2003 ), setting up both ends of life’s universal redox network. Indeed, redox-active phenols, quinones, flavins, and phenazines ( Bais et al., 2006 ; Tomilov et al., 2006 ; Uteau et al., 2015 ; Rasmann and Turlings, 2016 ) are prevalent in the rhizosphere where redox active processes have been highlighted in biofilm biogeography ( Stacy et al., 2014 ), allelopathy ( Tomilov et al., 2006 ), quorum sensing ( Fuller et al., 2017 ), and most notably, in the critical spatiotemporal dynamics of semagenesis ensuring success of the parasitic plants ( Keyes et al., 2007 ; Liang et al., 2016 ; Fuller et al., 2017 ). The initial discoveries of the reaction diffusion dynamics of semagenesis ( Chang et al., 1986 ; Fate et al., 1990 ; Smith et al., 1990 ) motivated further explorations of model reaction-diffusion systems in the rhizosphere ( Taran et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Article formation, and many other phenotypes with significance to host-microbial associations, microbial ecology, and more (Miller and Bassler, 2001). QS has emerged as a convergent strategy among various microorganisms as a way to couple phenotypic switching to cell density (Fuller et al, 2017). However, while prevalent in fungi, there are no examples of this phenomenon among other eukaryotes.…”
Section: Ll Open Access Isciencementioning
confidence: 99%